ANALYSIS OF PERCEIVED CAUSES AND FACTORS INFLUENCING VEGETABLE FARMERS-PASTORALISTS CONFLICTS IN KADUNA STATE, NIGERIA - Lawal Bello; Sani, M. H.; Abu, I. A.; Danwanka, H. A. (Journal of Agripreneurship and Sustainable Development, 2021)
The study was carried out on analysis of perceived causes and factors influencing vegetable farmers-pastoralists conflicts in Kaduna State, Nigeria. Multi-stage sampling procedure was employed to select 360 respondents from the study areas of Northern, Southern and Central Senatorial districts of Kaduna State. Data were collected through structure questionnaire and analyzed using descriptive (mean, frequency distribution, percentages and standard deviation) and inferential statistics (logistics regression). The results showed that 80.6% and 91.6% of the vegetable farmers and pastoralists were found to be male, majority (80.2%) and (86.1%) were married farmers and pastoralists, respectively. Also, the vegetable famers and pastoralists had relatively higher education of 34.1% and 31.8%, respectively. A grand mean of 3.79 was revealed as the perceived causes of vegetable farmers-pastoralists conflicts meaning there was persistence conflicts in the study area. So, the results disclosed the major causes of farmer-pastoralists conflicts to include influx of migrant herders/transhumance and night grazing (= 4.32), inadequate grazing reserve (= 4.25) and destruction of crop by animals (= 4.24) as perceived by vegetable farmers. However, the pastoralists perceived major causes of conflicts to include inadequate grazing reserve (= 4.44), destruction crops by animals (= 4.21) and encroaching grazing reserves (= 4.11). The results of logit regression on factors influencing farmers-pastoralists showed that age, and widow, number of livestock were found to be positively significant (P≤0.01), respectively. Household size, educational level and farm size were significant (P≤0.05) in influencing conflicts. The coefficient (-0.16) of number of livestock was found to be negative but significant (P≤0.01) implying that as number of livestock increases, the tendency to participate in a conflict also increases.it was concluded that vegetable farmers-pastoralists conflicts in the study was mostly influenced by age, education level, household size, farm size and number of livestock. The study recommended that grazing areas should be provided for pastoralists as a means of preventing farmers and pastoralist conflicts like the ranching (ruga) policy by the federal government and private partners.